2006
DOI: 10.1380/ejssnt.2006.258
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of Pd Nanoparticles

Abstract: A size and condensation controlled Pd nanoparticle is reported. The Pd nanoparticles are prepared by a gas condensation method with He gas, so called dry process. A fabrication of the nanoparticle by means of the dry process is an excellent way, because there are little contaminations on the most lateral surface of the nanoparticle than the nanoparticle by the wet process. Characterizations by TEM and AFM show that the fabricated Pd nanoparticle has a spherical shape, a few nm size in diameter and highly dispe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 12 publications
0
25
1
Order By: Relevance
“…It has been reported that Pd NPs surface is easily oxidized than that of bulk Pd by atmospheric components [10,11]. Therefore, we needed to connect the nanoparticle fabrication chamber of the gas evaporation method to the XPS measurement chamber.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that Pd NPs surface is easily oxidized than that of bulk Pd by atmospheric components [10,11]. Therefore, we needed to connect the nanoparticle fabrication chamber of the gas evaporation method to the XPS measurement chamber.…”
Section: Methodsmentioning
confidence: 99%
“…To clear these problems, it is necessary to fabricate Pd nanoparticles without surfactant molecules by the gas evaporation method [10,11] and to reveal adsorption reaction of sulfur-containing molecules adsorbed on nanoparticle surface.…”
Section: Introductionmentioning
confidence: 99%
“…The Pd NPs can be oxidized in even if under the ambient condition [11], whereas the Pd bulk possesses the good resistance against the oxidation. The surfactants or polymers protect the surface of the Pd NPs in the previous works [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The repeatability of the hydrogen absorption reveals the irreversibility of the hydrogenation reaction in the Pd NPs. The Pd NPs have been fabricated by the gas evaporation method using Helium (He) gas [11]. The clean surface of the Pd NPs can be obtained by the aggregation of the Pd atoms under the He gas atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…To fabricate nanoparticles with clean surface, we have used the gas evaporation method with noble gas [4,5]. Fabrication of Pd nanoparticles, which belongs to the platinum group metals, was successful with the method with He in our previous studies [6,7]. Therefore, we have focused on the adsorption reaction between Pd nanoparticles and the L-cysteine under water environment.…”
Section: Introductionmentioning
confidence: 99%